Fully automated and colorimetric foodborne pathogen detection on an integrated centrifugal microfluidic device. Issue 10 (26th April 2016) - Oh, Seung Jun; Park, Byung Hyun; Choi, Goro; Seo, Ji Hyun; Jung, Jae Hwan; Choi, Jong Seob; Kim, Do Hyun; Seo, Tae Seok
Abstract : This work describes fully automated and colorimetric foodborne pathogen detection on an integrated centrifugal microfluidic device, which is called a lab-on-a-disc. Abstract : This work describes fully automated and colorimetric foodborne pathogen detection on an integrated centrifugal microfluidic device, which is called a lab-on-a-disc. All the processes for molecular diagnostics including DNA extraction and purification, DNA amplification and amplicon detection were integrated on a single disc. Silica microbeads incorporated in the disc enabled extraction and purification of bacterial genomic DNA from bacteria-contaminated milk samples. We targeted four kinds of foodborne pathogens ( Escherichia coli O157:H7, Salmonella typhimurium, Vibrio parahaemolyticus and Listeria monocytogenes ) and performed loop-mediated isothermal amplification (LAMP) to amplify the specific genes of the targets. Colorimetric detection mediated by a metal indicator confirmed the results of the LAMP reactions with the colour change of the LAMP mixtures from purple to sky blue. The whole process was conducted in an automated manner using the lab-on-a-disc and a miniaturized rotary instrument equipped with three heating blocks. We demonstrated that a milk sample contaminated with foodborne pathogens can be automatically analysed on the centrifugal disc even at the 10 bacterial cell level in 65 min. The simplicity and portability of the proposed microdevice would provide an advanced platform for point-of-care diagnostics of foodborne pathogens, where prompt confirmation of food quality is needed.